2023
DOI: 10.1128/spectrum.05258-22
|View full text |Cite
|
Sign up to set email alerts
|

Digital PCR Discriminates between SARS-CoV-2 Omicron Variants and Immune Escape Mutations

Abstract: Spike mutations in the SARS-CoV-2 genome confer resistance to therapeutic monoclonal antibodies. Authorization for treatment options is typically guided by general trends of variant prevalence.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Similarly, its reliability has been demonstrated in the detection of both SARS-CoV-2 as a whole and of SARS-CoV-2 viral mutants that may be associated with increased antiviral resistance or atypical behaviour from the pathogenic or diagnostic point of view [6,26,27]. Thus, some studies have shown that dPCR would detect between 2.2 and 3.7 copies/reaction [27] and, compared to RT-qPCR, would increase the positive rate by 12.0% in samples from SARS-CoV-2 infected patients [27].…”
Section: Virology Applicationsmentioning
confidence: 97%
“…Similarly, its reliability has been demonstrated in the detection of both SARS-CoV-2 as a whole and of SARS-CoV-2 viral mutants that may be associated with increased antiviral resistance or atypical behaviour from the pathogenic or diagnostic point of view [6,26,27]. Thus, some studies have shown that dPCR would detect between 2.2 and 3.7 copies/reaction [27] and, compared to RT-qPCR, would increase the positive rate by 12.0% in samples from SARS-CoV-2 infected patients [27].…”
Section: Virology Applicationsmentioning
confidence: 97%
“…Diagnostic screening nucleic acid amplification technique (NAAT)-based assays are used as an alternative method that enables the early detection and pre-screening of VOCs. Recently, PCR-based studies have been published to address the diagnosis of SARS-CoV-2 variants [ 7 , 8 , 9 , 10 , 11 ]. Holand et al showed that the use of digital PCR will enable the need for a personalized diagnosis aimed at individual patient treatment [ 8 ], and Vogels et al aimed to reduce false negative results by multiplexed RT-PCR, developing a set of dedicated primers for variants sharing common mutations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PCR-based studies have been published to address the diagnosis of SARS-CoV-2 variants [7][8][9][10][11]. Holand et al showed that the use of digital PCR will enable the need for a personalized diagnosis aimed at individual patient treatment [8], and Vogels et al aimed to reduce false negative results by multiplexed RT-PCR, developing a set of dedicated primers for variants sharing common mutations [12].…”
Section: Introductionmentioning
confidence: 99%